The development of the German public mind. A social history of German political sentiments, aspirations and ideas (Allen & Unwin)
With indices. Tome 3 published under the title: Hertz, Frederick, The German public mind in the nineteenth century. 1. The Middle Ages. The Reformation. [1957]. IV, 525 p